Preliminary psychometric validation of the teammate burnout questionnaire - Appleby, R.; Davis, P. A.; Davis, L.; Stenling, A.; Vickery, W. (Frontiers in Psychology, 2022)
The aim of the present study was to provide support for the validation of the Teammate Burnout Questionnaire (TBQ). Athletes from a variety of team sports (N = 290) completed the TBQ and the Athlete Burnout Questionnaire (ABQ). Confirmatory factor analysis revealed acceptable fit indexes for the three-dimensional models (i.e., physical and emotional exhaustion, sport devaluation, reduced accomplishment) of the TBQ and the ABQ. Multi-trait multi-method analysis revealed that the TBQ and ABQ showed acceptable convergent and discriminant validity. The preliminary validation of the TBQ indicates the utility of the scale to reflect athletes` perceptions of their teammates` burnout and offers researchers the opportunity to quantitatively assess an important aspect of the social environment in the development of athlete burnout.